Pendampingan Pengelolaan Potensi Desa Oleh Masyarakat di Desa Puntuk Rejo Kecamatan Ngargoyoso Kabupaten Karanganyar - Winarti; Aris Triharyanto; Budiman Widodo (JURNAL ABDIMAS SERAWAI, 2022)
Village potential is an asset owned by the village that can be utilized as the village's ability in order to realize community welfare. The development of village potential is only intended for the benefit of the community. Of course, every village has this potential, because the potential of the village/region is all natural resources, resources as a result of development, and human resources. Puntuk Rejo Village is one of the villages in the Ngargoyoso District, Karanganyar Regency, Karanganyar Regency, Central Java, this village has beautiful natural beauty, this is supported by its location on the slopes of Mount Lawu with an altitude of 700 above sea level (m), cool air, so that the potential of Puntuk Rejo village to be developed is the agricultural and tourism sectors. This causes the area to be visited by many tourists both from the surrounding area and from outside the area, who want to enjoy the beauty of nature. The fertile agricultural sector is where the people of Puntuk Rejo village make a living as farmers, vegetables, and other crops, such as rice, polowijo, which can support tourism in the village. and the people who use these natural resources. The attraction of Puntuk Rejo village which encourages some people to want to own assets, especially land in the village, especially people who have money (capital), To build tourist attractions as new tourist destinations. This is the concern of the community service team, so they seek to provide assistance to the community in managing village potential, with the aim that in an effort to develop village potential, the Puntuk Rejo village community can enjoy, play an active role, so that the goals of Village Potential Development are planned by the government. village, district and provincial governments really prosper the community, especially the people of Puntuk Rejo village